The Own-Race Bias for Face Recognition in a Multiracial Society - Wong, Hoo Keat; Stephen, Ian D.; Keeble, David R. T. (Frontiers in Psychology, 2020)
The own-race bias (ORB) is a reliable phenomenon across cultural and racial groups where unfamiliar faces from other races are usually remembered more poorly than own-race faces (Meissner & Brigham, 2001). By adopting a yes/no recognition paradigm, we found that the ORB was pronounced across race groups (Malaysian-Malay, Malaysian-Chinese, Malaysian-Indian, and Western-Caucasian) when faces were presented with only internal features (Experiment 1), implying that growing up in a profoundly multi-racial society does not necessarily eliminate the ORB. Using a procedure identical to Experiment 1, we observed a significantly greater increment in recognition performance for other-race faces than for own-race faces when the external features (e.g., facial contour and hairline) were presented along with the internal features (Experiment 2) – this abolished the ORB. Contrary to assumptions based on the contact hypothesis, participants’ self-reported amount of interracial contact on a social contact questionnaire did not significantly predict the magnitude of the ORB. Overall, our findings suggest that the level of exposure to other-race faces accounts for only a small part of the ORB. In addition, the present results also support the notion that different processing mechanisms may be involved for own- and other-race faces, with internal features of own-race faces being processed more effectively whereas external features dominate representations of other-race faces.